Microbial Niche Diversification in the Galápagos Archipelago and Its Response to El Niño - Gifford, Scott M.; Zhao, Liang; Stemple, Brooke; DeLong, Kimberly; Medeiros, Patricia M.; Seim, Harvey; Marchetti, Adrian (Frontiers in Microbiology, 2020)
The Galápagos Archipelago is located at the intersection of several major oceanographic features that produce diverse environmental conditions around the islands, and thus has the potential to serve as a natural laboratory for discerning the underlying environmental factors that structure marine microbial communities. Here we used quantitative metagenomics to characterize microbial communities in relation to archipelago marine habitats, and how those populations shift due to substantial environmental changes brought on by El Niño. Environmental conditions such as temperature, salinity, inorganic dissolved nutrients, and dissolved organic carbon (DOC) concentrations varied throughout the archipelago, revealing a diversity of potential microbial niches arising from upwelling, oligotrophic to eutrophic gradients, physical isolation, and potential island mass effects. The volumetric abundances of microbial community members shifted with these environmental changes and revealed several taxonomic indicators of different water masses. This included a transition from a Synechococcus dominated system in the west to an even mix of Synechococcus and Prochlorococcus in the east, mirroring the archipelago’s mesotrophic to oligotrophic and productivity gradients. Several flavobacteria groups displayed characteristic habitat distributions, including enrichment of Polaribacter and Tenacibaculum clades in the relatively nutrient rich western waters, Leeuwenhoekiella spp. that were enriched in the more nutrient-deplete central and eastern sites, and the streamlined MS024-2A group found to be abundant across all sites. During the 2015/16 El Niño event, both environmental conditions and microbial community composition were substantially altered, primarily on the western side of the archipelago due to the reduction of upwelling from the Equatorial Undercurrent. When the equatorial upwelling resumed, concentrations of inorganic nutrients and DOC at the western surface sites were more typical of mesopelagic depths. Correspondingly, Synechococcus abundances decreased by an order of magnitude, while groups associated with deeper water masses were enriched, including streamlined roseobacters HTCC2255 and HIMB11, Thioglobacaceae, methylotrophs (Methylophilaceae), archaea (Nitrosopumilaceae), and distinct subpopulations of Pelagibaceriales (SAR11 clade). These results provide a quantitative framework to connect community-wide microbial volumetric abundances to their environmental drivers, and thus incorporation into biogeochemical and ecological models.